The role of flexible labour arrangements in the formalization of artisanal and small-scale mining: the case of Rwanda - Rushemuka, Maxime (Conjonctures de l’Afrique centrale, 2024)
Over the past fifteen years, Rwanda has made significant progress in formalizing mining rights and the production processes of 3Ts minerals in its artisanal and small-scale mining (ASM) sector. However, labour relations remain largely unregulated. This study analyses ASM activities through the production process observations, document reviews, and interviews with key informants involved in the sector's liberalization and formalization. It highlights the persistence of diverse and informal labour relationships between employers and miners, including the use of non-standardized remuneration methods. The discussions go beyond the narratives of qualifying informal labour relations as “formalization shortcomings” found in ASM literature. Instead, the study reveals that flexible labour arrangements were essential for the success of Rwanda’s formalization efforts, helping mitigate investor risks. The regulation of these labour relations would have otherwise discouraged investment in formal mines. Informal labour conditions, however, weaken miners' positions, limiting their legal or administrative recourse against injustices. Despite this, formal ownership has imposed certain responsibilities on mine owners toward their workers, particularly regarding ensuring their safety on mining sites. The study concludes that in contexts like Rwanda’s, acknowledging the limitations of labour formalization and focusing on regulating other aspects of ASM may be more effective in improving miners' conditions.
Keywords: 3Ts; Rwanda; formalization; labour relations